Risiko Geopolitik dan Indeks Harga Saham Gabungan Indonesia - Saputra, Sahdan; Marswandi, Ega Dwi Putri; Hendri, Wira (Jurnal Ekonomi Manajemen Perbankan, 2024)
The escalating global geopolitical tensions have garnered significant attention from researchers and practitioners. This study investigates the impact of domestic geopolitical risks and the influence of countries with the highest geopolitical index, namely Ukraine, America, Russia, and China, on the Indonesian composite stock price index. Employing geopolitical risk index (GPRH) and geopolitical action (GPRA) data spanning from January 2004 to October 2023, the analysis is based on 238 observations. The findings reveal that Ukraine and America exert a negative and significant influence, while China and Russia demonstrate a positive and significant impact on the index. Moreover, the study underscores that the influence of geopolitical risk on the Indonesian stock market is more pronounced during periods of heightened geopolitical activity, such as escalating conflicts and acts of terror. These results suggest that investors should carefully consider geopolitical risks when making investment decisions.